Performance on rheumatoid arthritis quality indicators in an Alaska Native healthcare system. Issue 5 (23rd July 2010) - Ferucci, Elizabeth D; Donnithorne, Katherine J; Koller, Kathryn R; Swango-Wilson, Amy; Pflaum, Jacqueline; Lanier, Anne P
Abstract : Objective: Rheumatoid arthritis (RA) is highly prevalent in some Alaska Native and American Indian populations. Quality indicators for RA have been proposed, but these have not been widely implemented or used to assess RA care in Alaska Native or American Indian populations. Methods: Medical records were included if they met the following criteria: RA diagnosed before October 2000 fulfilling American College of Rheumatology classification criteria; all care for RA at the Alaska Native Medical Center. Records were reviewed for a 5-year period to determine compliance with eight quality indicators defined by the Arthritis Foundation Quality Indicator Program. Multivariate logistic regression was performed to analyse associations with quality of care. Results: There were 106 individuals included in the study. The highest-scoring measures were folic acid prescription if on methotrexate (93.3%) and disease-modifying antirheumatic drug prescription (90.6%). The lowest scoring measure was radiographs of both hands and feet (16.0%). In multivariate analysis, the factor most strongly associated with disease-modifying antirheumatic drug prescriptions, annual exam for RA and hand radiographs was at least one visit with a rheumatologist. Conclusions: Quality of care for RA varies by measure and is better for patients who see a rheumatologist. These data provide an initial evaluation of RA quality of care in a unique minority population with an integrated healthcare system.